COATINGS DISCRETE SURFACES CONSTRUCTION BY SUPERPOSITIONS OF ADJUSTED MESH FRAMES - Vorontsov, O. V.; Tulupova, L. O.; Vorontsova, I. V. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The method of curve surface discrete geometric modeling on the basis of two discrete frames superimpositions, formed by a static-geometric method, and on the basis of a single surface curve nodal points superimposition, also formed by static-geometric method, is considered. It has been determined that the suggested method allows to model balanced discrete structures formed on the specified contour nodes, as well as those passing through the specified nodal points without composing and solving equations systems.